Propolis augments apoptosis induced by butyrate via targeting cell survival pathways. - Eric Drago; Michael Bordonaro; Seon Lee; Wafa Atamna; Darina L Lazarova (PLoS ONE)
Diet is one of the major lifestyle factors affecting incidence of colorectal cancer (CC), and despite accumulating evidence that numerous diet-derived compounds modulate CC incidence, definitive dietary recommendations are not available. We propose a strategy that could facilitate the design of dietary supplements with CC-preventive properties. Thus, nutrient combinations that are a source of apoptosis-inducers and inhibitors of compensatory cell proliferation pathways (e.g., AKT signaling) may produce high levels of programmed death in CC cells. Here we report the combined effect of butyrate, an apoptosis inducer that is produced through fermentation of fiber in the colon, and propolis, a honeybee product, on CC cells. We established that propolis increases the apoptosis of CC cells exposed to butyrate through suppression of cell survival pathways such as the AKT signaling. The programmed death of CC cells by combined exposure to butyrate and propolis is further augmented by inhibition of the JNK signaling pathway. Analyses on the contribution of the downstream targets of JNK signaling, c-JUN and JAK/STAT, to the apoptosis of butyrate/propolis-treated CC cells ascertained that JAK/STAT signaling has an anti-apoptotic role; whereas, the role of cJUN might be dependent upon regulatory cell factors. Thus, our studies ascertained that propolis augments apoptosis of butyrate-sensitive CC cells and re-sensitizes butyrate-resistant CC cells to apoptosis by suppressing AKT signaling and downregulating the JAK/STAT pathway. Future in vivo studies should evaluate the CC-preventive potential of a dietary supplement that produces high levels of colonic butyrate, propolis, and diet-derived JAK/STAT inhibitors.